Gambaran Input Program Pelayanan Obstetri dan Neonatal Emergensi Dasar (PONED) di Puskesmas Silo I Jember - Anis Satu Rohmah; Christyana Sandra; Yennike Tri Herawati (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Complications in pregnancy and childbirth can not be predicted. One of the efforts to improve obstetric complications prevention services is strengthening PONED. A Primary Health Care that experienced of an increase in Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) cases is Silo I Primary Health Care. The study aimed to describe the input of the Basic Emergency Obstetric and Neonatal Service (BEONEC) program at the Silo I Primary Health Care in Jember. The result showed that the availability of human resources has not been in accordance with established guidelines. The PONED team has not been in service for 24 hours. The financing does not have special PONED fund allocation. The availability of medicines for obstetrical and neonatal consumables in the category is sufficiently available. The available room is limited. Medical and non-medical equipment are complete enough to carry out emergency services. Supporting facilities are available in full at the health center. Silo I Health Center has a Standard Operating Procedure (SOP) with a complete category.